Lymphocyte-t type th1 and th2 activity difference of lung tissue on heligmosomoides polygyrus nematode and mycobacterium tuberculosis sequential co-infection - Wulandari, Laksmi; Amin, Muhammad; Soedarto, Soedarto; Soegiarto, Gatot (Folia Medica Indonesiana, 2017)
Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis that are often associated with uneffectiveness of the BCG vaccine and the high worm infection. The objective of this study was to determine the differences in the activity of Limfosit T type Th1 (IFN-g) and Th2 (IL-4) in lung tissue on Heligmosomoides polygyrus nematode and Mycobacterium tuberculosis sequential co-infection. This research using 49 mice were divide into 7 groups treated with infection by Mycobacterium tuberculose inhaled and Heligmosomoides polygyrus orally within 8 and 16 weeks. The levels of IFN-g in peripheral blood serum (89.929 + 3.533 pg/mL) resembles the pattern of the percentage of lymphocytes T CD4+ Th1 in lung tissue (3.246 + 0.519%) and peripheral blood (4.950 + 0.237%), while the levels IL-4 in the peripheral blood serum (20.782 + 4.043%) resembles the pattern of the percentage of lymphocytes T CD4+ Th2 in intestinal tissue (1.048 + 0.359%) and peripheral blood (1.196 + 0.557%). In conclusion, there is difference in the activity of lymphocytes T type Th1 and Th2 but it does not affect the immune response to Mycobacterium tuberculosis infection.